2013
DOI: 10.3109/15563650.2013.841180
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with severe effects following acute glufosinate poisoning

Abstract: Severe effects following acute glufosinate poisoning were associated with two positive SIRS criteria. A low P/F ratio may be useful for predicting the occurrence of respiratory complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 17 publications
0
25
1
Order By: Relevance
“…Therefore, we propose that clinicians should check initial serum ammonia levels to predict the likelihood of neurologic complications in glufosinate-poisoned patients admitted to the ED. Inoue, et al 6 reported that severe complications following acute glufosinate poisoning were associated with two positive cases of systemic inflammatory response syndrome (SIRS); however, we did not detect any differences between patient groups in terms of the two positive SIRS criteria ( Table 1 ). Further investigations will be needed.…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations
“…Therefore, we propose that clinicians should check initial serum ammonia levels to predict the likelihood of neurologic complications in glufosinate-poisoned patients admitted to the ED. Inoue, et al 6 reported that severe complications following acute glufosinate poisoning were associated with two positive cases of systemic inflammatory response syndrome (SIRS); however, we did not detect any differences between patient groups in terms of the two positive SIRS criteria ( Table 1 ). Further investigations will be needed.…”
Section: Discussioncontrasting
confidence: 85%
“…In our study, the sample was enriched in terms of patients with severe disturbance of consciousness (60.0%) and seizure (51.1%) unlike the samples used in Mao, et al 12 and Inoue, et al 6 (20.9% and 50.0%, 8.7%, and 18.8%), respectively. Between our study, the Mao, et al 12 study, and the Inoue, et al 6 study, there were no significant differences in terms of age and ingested amounts [62±15 yrs vs. 60 (IQR 40-72) yrs vs. 74 (IQR 65-86) yrs; 27.0 (IQR 18.0-54.0) g vs. 30.4 (IQR 18.5-45.6) g vs. 27.8 (IQR 9.3-55.5) g]. The results of this study indicate that acute glufosinate poisoning can cause complications much more often than previously reported.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Glufosinate inhibits the synthesis of glutamine in plants, and plant death occurs as a consequence of the increased ammonia levels [16]. Glufosinate supress the activity of glutamine synthetase and glutamate decarboxylase, reducing glutamic acid levels and elicits various types of moderate-to-severe CNS toxicities [51]. Given the differences in the biochemical and metabolic pathways of plants and mammals, glufosinate ammonium formulations are minimally toxic to humans [52].…”
Section: Glycine Derivativesmentioning
confidence: 99%